2006
DOI: 10.1080/00365520500320094
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of inflammatory bowel disease in Primorsko-goranska County, Croatia, 2000–2004: A prospective population-based study

Abstract: The incidence of IBD was higher than previously observed in Croatia. Our results suggest that CD incidence rates in the northern coastal part of Croatia are currently comparable with those reported in northern Europe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(21 citation statements)
references
References 27 publications
2
17
1
1
Order By: Relevance
“…It would be more accurate to compare incidence rates in whole countries, for example, Spain and Croatia (although it is not precise enough for absolutely correct analysis). The same reflection may be also right in the case with study of Boraska Jelavic et al; but there we also cannot assess the correctness of the relation between UC and CD incidence rates in the Split and in the location where Sincić et al [114] conducted their research.…”
Section: Tlr4 Polymorphisms and Colorectal Cancermentioning
confidence: 69%
See 2 more Smart Citations
“…It would be more accurate to compare incidence rates in whole countries, for example, Spain and Croatia (although it is not precise enough for absolutely correct analysis). The same reflection may be also right in the case with study of Boraska Jelavic et al; but there we also cannot assess the correctness of the relation between UC and CD incidence rates in the Split and in the location where Sincić et al [114] conducted their research.…”
Section: Tlr4 Polymorphisms and Colorectal Cancermentioning
confidence: 69%
“…However, further analysis shows that this hypothesis is also evidently incorrect. The case sample in the study of Landi et al was recruitred in Spain in 1996 -1998, and the incidence rates of UC and CD at this period were similar to Croatian, where the research of Boraska Jelavic et al was brought about (7-9.3*10 5 for UC and 4.8 -6.08*10 5 for CD in Spain [113], 4.3*10 5 for UC and 7.0*10 5 for CD in Croatia [114]). …”
Section: Tlr4 Polymorphisms and Colorectal Cancermentioning
confidence: 75%
See 1 more Smart Citation
“…On the other hand, some studies on ulcerative colitis incidence suggest that, although the overall incidence of ulcerative colitis has stabilized, it continues to rise in males, with a corresponding decrease in T a b l e 1 . T h e Nu mb e r o f Ul c e r a t i v e Co l i t i s P a t i e n t s : Ma l e s , F e ma l e s , o r Ur b a n , a n d Ru r a l Dwe l l e r s (14), but another reported that the incidence rates of ulcerative colitis are almost the same in Spanish urban and rural populations (15).…”
Section: Ulcerative Colitis and Crohn's Disease Are Collectively Refementioning
confidence: 99%
“…Past studies have estimated CD incidence rate in Europe between 2.5 and 7.5 cases/100,000 inhabitants/year (1-3); however, the rate has been increasing in recent years, with the latest estimates being around 9 cases/100,000 inhabitants/year (4)(5)(6)(7). CD is usually diagnosed during young adulthood, and the mortality rate, although higher than that of the overall population, is not very high.…”
Section: Introductionmentioning
confidence: 99%